Economic evaluation of the intellectual and innovative activity of enterprises - Nagy, Szabolcs; Kobielieva, T. O.; Pererva, P. G. (ТОВ "Юридична компанія "Юрсервіс", 2023)
It is proposed to carry out a quantitative assessment of intellectual and innovative activity based on three main approaches: functional, effective and factor-resultative.
Економічна оцінка інтелектуально-інноваційної діяльності підприємств
Keywords: business; economy; intellectual and innovative activity; economic assessment; enterprises